PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL STAD BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS IV SDN 27 PENJA - Nurul Risdayanti; Hasan; Muhammad Nasrul (STKIP Subang, 2026)
This study aimed to determine whether there was an improvement in students’ learning outcomes after the implementation of the STAD cooperative learning model assisted by picture media. The background of this study was based on the low level of students’ understanding and participation in Social Studies learning, which resulted in many students achieving scores below the Minimum Mastery Criteria (KKTP). This research employed Classroom Action Research (CAR) consisting of two cycles, with each cycle comprising two meetings. The results showed an improvement in both students’ learning outcomes and participation in each cycle. In Cycle I, the average score reached 70.67 with a learning mastery percentage of 60%, while in Cycle II, the average score increased to 86.67 with a mastery percentage of 86.7%. In addition, the observation results of students’ activity improved from 62.5% in Cycle I to 82.5% in Cycle II. These findings indicate that the implementation of the STAD cooperative learning model assisted by picture media was effective in enhancing students’ engagement and learning outcomes. Therefore, this study provides a positive contribution for teachers in selecting appropriate learning models and media to create a more active, engaging, and meaningful learning environment, particularly on the topic of roles and responsibilities in the school and community environment.